Kinematic aspects of robotic biped locomotion systems - Silva, Filipe M. (1997)
This paper presents the kinematic study of robotic biped locomotion systems. The main purpose is to determine the kinematic characterisitcs and the system performance during walking. For that objective, the prescribed motino of the biped is completely characterised in terms of five locomotion variables: step length, hip height, maximum hip ripple, maximum foot clearance and link lengths. In this work, we propose three methods to quantitatively measure the performance of the walking robot: locomobility measure, perturbation analysis. and lowpass frequency response. These performance measures are discussed and compared in determining the robustness and effectiveness of the resulting locomotion.